Risk Management Analysis in Container Yard Development Projects in Eastern Indonesia - Prafajar Suksessanno Muttaqin; Nia Novitasari; Erlangga Bayu Setyawan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
A container yard is a place for storing containers, a place for cleaning, and repairs, as well as a place for carrying out container surveys. Currently planning the construction of a container yard in Eastern Indonesia is being carried out. In its construction, a container yard requires large investment costs due to many factors such as the difficulty and high cost of transporting raw materials, permits that require planning, to the need for proper business processes in order to provide smooth operational activities by minimizing risk. The purpose of this study is to identify the risks and causes of risks involved in the container depot development project in Eastern Indonesia using the quantitative risk assessment (QRA) method, so as to provide the most influential risk management recommendations. The research succeeded in identifying 24 risks and 24 causes of risk. Furthermore, from the calculation results, it was concluded that there were 9 most influential risks. Depo kontainer merupakan tempat penyimpanan kontainer, tempat pembersihan, perbaikan, serta tempat untuk pelaksanaan survei kontainer. Saat ini sedang dilakukan perencanaan pembangunan depo kontainer di Indonesia Timur. Dalam pembangunanya, depo kontainer membutuhkan biaya investasi yang besar yang disebabkan banyak faktor seperti sulit dan tingginya biaya transportasi bahan baku, perizinan yang membutuhkan perencanaan, hingga kebutuhan akan adanya proses bisnis yang tepat agar dapat memberikan kelancaran pada aktivitas operasional dengan meminimasi risiko. Tujuan penelitian ini adalah mengindenfitikasi risiko dan penyebab risiko yang terdapat pada proyek pembangunan depo kontainer di Indonesia Timur dengan metode quantitative risk assessment (QRA), sehingga dapat memberikan usulan penanganan risiko yang paling berpengaruh. Penelitian berhasil mengidentifikasi 24 risiko dan 24 penyebab risiko. Lebih lanjut dari hasil perhitungan disimpulkan ada 9 risiko paling berpengaruh.